Theranostics of Gold Nanoparticles with an Emphasis on Photoacoustic Imaging and Photothermal Therapy - Liu, Yi; Ma, Wenhui; Wang, Jing (Current Pharmaceutical Design, 2018)
Gold nanoparticles (AuNPs) are promising biomedical agents in terms of both imaging and therapy, exhibiting excellent physical and chemical characteristics. The actions of AuNPs can be remotely controlled using strong near-infrared (NIR) light, associated with minimal lateral invasion. Employing the photoacoustic (PA) principle, AuNPs integrate imaging and temperature control, affording both diagnosis and treatment mediated by NIR light. We here review recent progress in the theranostic field employing AuNPs to both PA and photothermal ends.
Keywords: theranostics